2003
DOI: 10.1038/nm826
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C blocks p53-mediated apoptosis in ischemic human brain endothelium and is neuroprotective

Abstract: Activated protein C (APC) is a systemic anti-coagulant and anti-inflammatory factor. It reduces organ damage in animal models of sepsis, ischemic injury and stroke and substantially reduces mortality in patients with severe sepsis. It was not known whether APC acts as a direct cell survival factor or whether its neuroprotective effect is secondary to its anti-coagulant and anti-inflammatory effects. We report that APC directly prevents apoptosis in hypoxic human brain endothelium through transcriptionally depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
587
0
8

Year Published

2003
2003
2008
2008

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 550 publications
(628 citation statements)
references
References 31 publications
33
587
0
8
Order By: Relevance
“…In the PROWESS trial, sepsis patients that were treated with APC have a steady-state level of 45 ng/ ml [45]. However, our overall goal was to characterize the mechanism of APC to promote cell migration and we used similar APC concentrations as in previous in vitro studies (0.5-50 μg/ml) [20,26,29]. Interestingly, levels of APC used in HUVEC experiments are closer to physiological concentrations of APC (0.1-10 μg/ml) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the PROWESS trial, sepsis patients that were treated with APC have a steady-state level of 45 ng/ ml [45]. However, our overall goal was to characterize the mechanism of APC to promote cell migration and we used similar APC concentrations as in previous in vitro studies (0.5-50 μg/ml) [20,26,29]. Interestingly, levels of APC used in HUVEC experiments are closer to physiological concentrations of APC (0.1-10 μg/ml) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Using zymogen PC, chemically inactivated DEGR-APC, and an active site mutant of APC (S195A) with the MDA-MB-231 cancer cells, one finding of our study showed that the active protease was needed to increase cell migration. Therefore, unlike the inhibitory role of APC with lymphocytes, the pro-migratory role of APC in the MDA-MB-231 cells requires the active site of the protease, most likely to bind and activate receptors, such as PAR-1 [20,21,26,30,31], and to activate extracellular matrix proteases, such as MMP-2 and MMP-9 [27,46,47]. It is possible that when bound to EPCR, APC may undergo modifications to its macromolecular substrate recognition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations